Photocatalytic performance of activated carbon-supported mesoporous titanium dioxide - Bagheri, Samira; Mohd Hir, Z.A.; Termeh Yousefi, A.; Hamid, Sharifah Bee Abd (Taylor & Francis, 2016)
The photocatalytic activity of methyl orange (MO) in aqueous solution was studied using the hydrothermal synthesis of activated carbon-loaded TiO2 at different weight ratios. The hydrothermal process was conducted at a temperature of 180°C for 12 h in order to obtain a high surface area and porosity for the purpose of degradation activity. The results indicated that TiO2-PEG-Ac (0.50%) exhibited better photocatalytic performance compared to other prepared photocatalysts. The photodegradation process was observed to be pH dependent, since almost 100% of MO removal was possible in an acidic medium. In contrast, the degradation activity seems to be diminished in basic media. The overall photocatalytic activity of TiO2 was enhanced due to the presence of porous activated carbon as co-catalyst and support.